THE REFLECTION OF THE WORKING-CLASS LIFE CONDITIONS DURING THE VICTORIAN ERA FOUND IN OLIVER TWIST IN DICKENS’ OLIVER TWIST - Rusmini, Rusmini; Kuncara, Singgih Daru; Muhajir, Fatimah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2019)
This study examines Oliver Twist novel written by Charles Dickens as the object of the research. The aims of this research are to find out the conditions of working-class life during the Victorian era which are reflected in Oliver Twist novel, and to show the way Dickens reflected the conditions of working-class life during the Victorian era in Oliver’s life. This research uses the sociology of literature theory in analyzing the working-class life conditions in the novel. The method of this research belongs to qualitative research, using mimetic approach. The data of this research are words, phrases, sentences and paragraphs that indicated as the working-class life conditions as reflected in the novel. Then the result of the research shows there are seven characteristics of the working-class life condition as reflected in Dickens’ Oliver Twist such as the workhouse, fear and hopelessness, the smallest laborers, a difficult transition, an unsanitary life, crime in the city, and too much convicts; and the way Dickens reflected the working-class life conditions during the Victorian era in the novel through Oliver’s actions, dialogues, speech, thoughts, appearance and the narrations of the story.